2004
DOI: 10.1128/cdli.11.3.569-576.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Criteria for Interpretation of Immunoglobulin G Immunoblotting Results for Diagnosis of Helicobacter pylori Infection

Abstract: Gastric infection withHelicobacter pylori is one of the most common chronic infections in humans, causing substantial morbidity and mortality. The diagnosis of H. pylori infection usually involves upper endoscopy with biopsy since the only noninvasive method of comparable accuracy, the [ 13 C]urea breath test, requires technical equipment that is not available in most gastroenterological units. Serological methods for detection of H. pylori infection have reached sufficient accuracy to be used as screening tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…In spite of these potential advantages and the widespread availability of blotting equipment in clinical laboratories, Lepper et al (305) reported that immunoblot for H. pylori antibodies is not common practice and that this was possibly due to discrepant recommendations for interpretation. Indeed, most of the publications concerning this subject are merely descriptive (9,90,138,195,261,298,560), and only four proposed interpretation criteria (219, 407, 527, 559).…”
Section: Detection Of H Pylori Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of these potential advantages and the widespread availability of blotting equipment in clinical laboratories, Lepper et al (305) reported that immunoblot for H. pylori antibodies is not common practice and that this was possibly due to discrepant recommendations for interpretation. Indeed, most of the publications concerning this subject are merely descriptive (9,90,138,195,261,298,560), and only four proposed interpretation criteria (219, 407, 527, 559).…”
Section: Detection Of H Pylori Antibodiesmentioning
confidence: 99%
“…Indeed, the immunoblot is most likely used as a second-step technique to identify false-positive cases detected by ELISA, in which case, the criteria proposed by Nillson et al (407) and Trautmann et al (527) leading to 100% specificity must be used. In contrast, when immunoblotting is used for preendoscopy screening, the criteria of Lepper et al, which emphasize sensitivity, are more suitable (305). A commercial immunoblot test is now available, which is an important advance toward standardization, Helicoblot 2.1 (Genelabs, Singapore) (305,383,432).…”
Section: Detection Of H Pylori Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that Lewis antigen expression enhances bacterial internalization by epithelial cells (374) suggests that Lewis antigen expression potentially affects the innate immune response. H. pylori LPS stimulates NF-B and IL-8 production in both epithelial cells and immune cells in a CagA-independent manner (53,359,384), but the NF-B activation observed in epithelial cells upon stimulation with H. pylori is not mediated by LPS (445). Compared to other gram-negative bacteria, the LPS of H. pylori is a poor activator of the innate immune response (59,446).…”
Section: Role Of H Pylori Virulence Factorsmentioning
confidence: 99%
“…Strains carrying the genes encoding the cytotoxin-associated protein (Cag-A) cause chronic active gastritis [2] . Gastric infection with H pylori is one of the common chronic infections in humans, causing substantial morbidity and some mortality [3] . Before an active protective response occurs, the gut must first be exposed to H pylori, which is a slowly growing microaerophilic, highly motile, Gramnegative spiral organism whose most striking biochemical characteristic is the abundant production of urease [4] .…”
Section: Introductionmentioning
confidence: 99%